Opioid overdose survivors: Medications for opioid use disorder and risk of repeat overdose in Medicaid patients. (1st March 2022) - Crystal, Stephen; Nowels, Molly; Samples, Hillary; Olfson, Mark; Williams, Arthur Robin; Treitler, Peter
Abstract: Background: Patients with medically-treated opioid overdose are at high risk for subsequent adverse outcomes, including repeat overdose. Understanding factors associated with repeat overdose can aid in optimizing post-overdose interventions. Methods: We conducted a longitudinal, retrospective cohort study using NJ Medicaid data from 2014 to 2019. Medicaid beneficiaries aged 12–64 with an index opioid overdose from 2015 to 2018 were followed for one year for subsequent overdose. Exposures included patient demographics; co-occurring medical, mental health, and substance use disorders; service and medication use in the 180 days preceding the index overdose; and MOUD following index overdose. Results: Of 4898 individuals meeting inclusion criteria, 19.6% had repeat opioid overdoses within one year. Index overdoses involving heroin/synthetic opioids were associated with higher repeat overdose risk than those involving prescription/other opioids only (HR = 1.44, 95% CI = 1.22–1.71). Risk was higher for males and those with baseline opioid use disorder diagnosis or ED visits. Only 21.7% received MOUD at any point in the year following overdose. MOUD was associated with a large decrease in repeat overdose risk among those with index overdose involving heroin/synthetic opioids (HR = 0.30, 95% CI = 0.20–0.46). Among those receiving MOUD at any point in follow-up, 10.5% (112/1065) experienced repeat overdose versus 22.1% (848/3833) for those without MOUD. Conclusions: Repeat overdose was common among individuals with medically-treated opioid overdose. Risk factors for repeat overdose varied by type of opioid involved in index overdose, with differential implications for intervention. MOUD following index opioid overdose involving heroin/synthetic opioids was associated with reduced repeat overdose risk. Highlights: 19.6% of participants had repeat medically-treated opioid overdose within one year. Overdoses involving heroin/fentanyl were associated higher risk of repeat overdose. A minority of participants received MOUD during follow-up. Receipt of MOUD was associated with two-thirds reduction in repeat overdose risk.